HETP Evaluation of Packing Laboratory Scale Distillation Column to Benzaldehyde Purification Process - Nguyen, Trung Dung; Phan, Ngoc Quang; Pham, Duc Anh; Do, Nguyen Ha Thu; Nguyen, Van Anh; Ta, Hong Duc; Cao, Hong Ha (JST: Engineering And Technology For Sustainable Development, 2022)
This study analyzes the literature on techniques for estimating HETP values for various packing structure models, ranging from theoretical to semi-empirical to shortcut methods. Packing structures of various meshes and shapes were studied on the purification of benzaldehyde from the mixture of benzaldehyde and cinnamaldehyde. The packing structures M-50, M-80, O-80, and S-80 were estimated using Fenske’s approach as 0.052, 0.053, 0.045, and 0.056, respectively. Experiment data and simulation result obtained by commercial software were utilized to validate the packing’s HETP value. A pilot of the vacuum batch distillation system was fabricated including a column filled with packing structures. The results indicated that the HETP value between experiment and simulation is within 0.6 percent deviation. On the pilot scale, the results of the benzaldehyde purifying were validated in a batch distillation system with the O-80 packing structure. This system will be developed for the larger scale, and it will very practical and useful.